Phosphorus deprivation affects composition and spatial distribution of membrane lipids in legume nodules. Issue 4 (13th January 2021) - Dokwal, Dhiraj; Romsdahl, Trevor B; Kunz, Daniel A; Alonso, Ana Paula; Dickstein, Rebecca
Abstract: In legumes, symbiotic nitrogen (N) fixation (SNF) occurs in specialized organs called nodules after successful interactions between legume hosts and rhizobia. In a nodule, N-fixing rhizobia are surrounded by symbiosome membranes, through which the exchange of nutrients and ammonium occurs between bacteria and the host legume. Phosphorus (P) is an essential macronutrient, and N2 -fixing legumes have a higher requirement for P than legumes grown on mineral N. As in the previous studies, in P deficiency, barrel medic ( Medicago truncatula ) plants had impaired SNF activity, reduced growth, and accumulated less phosphate in leaves, roots, and nodules compared with the plants grown in P sufficient conditions. Membrane lipids in M. truncatula tissues were assessed using electrospray ionization–mass spectrometry. Galactolipids were found to increase in P deficiency, with declines in phospholipids (PL), especially in leaves. Lower PL losses were found in roots and nodules. Subsequently, matrix-assisted laser desorption/ionization–mass spectrometry imaging was used to spatially map the distribution of the positively charged phosphatidylcholine (PC) species in nodules in both P-replete and P-deficient conditions. Our results reveal heterogeneous distribution of several PC species in nodules, with homogeneous distribution of other PC classes. In P poor conditions, some PC species distributions were observed to change. The results suggest that specific PC species may be differentially important in diverse nodule zones and cell types, and that membrane lipid remodeling during P stress is not uniform across the nodule. Abstract : ESI–MS and matrix-assisted laser desorption ionization–mass spectrometry imaging reveal alterations in Medicago truncatula nodules membrane lipid composition and spatial distribution in phosphorus deficiency.